A Customary Law (Adat Recht) Study on the Impact of Defense Policy on the Management of Right to Build (HGB) in the Property Sector - Muharman, Dedy (PT. Anagata Sembagi Education, 2025)
This study aims to normatively examine the impact of national defense policies on the existence and legal certainty of Building Use Rights (HGB) within the property sector, with a specific focus on areas overlapping with customary land. The establishment of strategic national zones by the government as part of defense planning frequently results in overlapping claims, legal ambiguity, and conflicts. These policies, while essential for national security, often disregard the socio-legal context of land ownership, particularly in regions inhabited or claimed by indigenous communities whose land tenure systems are rooted in customary law (adat). Through a statute approach, the research identifies significant disharmony among defense regulations, agrarian law, and laws recognizing indigenous peoples' rights. This legal fragmentation has resulted in inadequate protection for HGB holders and customary landowners, leading to heightened vulnerability, social tensions, and the systemic marginalization of local populations. Furthermore, the lack of inclusive consultation processes in defense-driven land designations exacerbates the problem. Thus, there is an urgent need for an integrated legal framework that harmonizes national defense objectives with land rights recognition and equitable development. Such reform should balance strategic interests, uphold the rule of law, and respect the rights of indigenous peoples to ensure sustainable and socially just land governance.